(untitled) (The Peerian Journal, 2023)
This article is devoted to the application of specialized software for visualizing temperatures in technological processes. The article discusses the main tasks that can be solved using software tools, such as monitoring the temperature regime, identifying deviations, optimizing equipment operation, and others. In conclusion, it is noted that the development of technology for visualizing parameters in technological processes will contribute to increasing production efficiency, reducing the risks of emergency situations, and improving the quality of the products produced.